Cardiac function, myocardial fat deposition, and lipid profile in young smokers: a cross-sectional study - Batista, Ana Natália Ribeiro; Garcia, Thaís; Prudente, Robson; Barbosa, Maurício F.; Modesto, Pamela; Franco, Estefânia; de Godoy, Irma; Paiva, Sergio; Azevedo, Paula; Tanni, Suzana Erico (Frontiers in Cardiovascular Medicine, 2023)
Background: There is a possibility that cardiac morphometric characteristics are associated with the lipid profile, that is, the composition and concentration of triglycerides, total cholesterol, HDL, LDL, and others lipoproteins in young smokers without comorbidities. Thus, this study aimed to evaluate the association of cardiac morphometric characteristics, myocardial fat deposition, and smoking cessation with the lipid profile of young smokers. Methods: A clinical and laboratory evaluation of lipids and the smoking status was performed on 57 individuals, including both a smoker group and a control group. Cardiac magnetic resonance imaging (MRI) with proton spectroscopy was performed to identify cardiac changes and triglyceride (TG) deposition in myocardial tissue. Results: No differences were observed between the groups (control vs smokers) in relation to the amount of myocardial TG deposition (p=0.47); however, when TG deposition was correlated with cardiac MRI variables, a positive correlation was identified between smoking history and myocardial TG deposition (hazard ratio [95% CI], 0.07 [0.03–0.12]; p=0.002). Furthermore, it was observed that the smoking group had lower high-density lipoprotein cholesterol (51 [45.5–59.5] mg/dL vs. 43 [36–49.5] mg/dL, p=0.003) and higher TG (73 [58–110] mg/dL vs. 122 [73.5–133] mg/dL, p=0.01) and very-low-density lipoprotein cholesterol (14.6 [11.6–22.2] mg/dL vs. 24.4 [14.7–26.6] mg/dL, p=0.01) values. In the control and smoking groups, a negative correlation between TGs and the diameter of the aortic root lumen and positive correlation with the thickness of the interventricular septum and end-diastolic volume (EDV) of both the right ventricle (RV) and left ventricle (LV) were noted. Moreover, in the RV, positive correlations with the end-systolic volume (ESV) index (ESVI), stroke volume (SV), ESV, and EDV were observed. Regarding serum free fatty acids, we found a negative correlation between their values and the diameter of the lumen of the ascending aortic vessel. Lipoprotein lipase showed a positive correlation with the SV index of the RV and negative correlation with the diameter of the lumen of the ascending aortic vessel. Conclusion: Several associations were observed regarding cardiac morphometric characteristics, myocardial fat deposition, and smoking cessation with the lipid profile of young smokers.